PERAN PANITIA KEGIATAN NUZULUL QUR’AN DALAM MEMBENTUK KARAKTER KEAGAMAAN REMAJA MASJID NURUL HAKIM DI DESA BANGUN KECAMATAN SAMPOLAWA - Asti Amalia; Maudin; Darmayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the role of the committee in the Nuzulul Qur'an activity as an effort to shape the religious character of adolescents at the Nurul Hakim Mosque in Bangun Village, Sampolawa District. Social changes influenced by globalization and the development of digital technology have also impacted adolescents' religious patterns, such as decreasing active involvement in mosque activities and weakening the internalization of religious values. This condition requires a contextual and participatory development strategy so that adolescents maintain a close relationship with religious activities. The Nuzulul Qur'an activity has the potential to be a medium for character formation if it is not only positioned as an annual ceremonial agenda, but also utilized as a social and religious learning space for adolescents. This study uses a qualitative approach with a descriptive research type. Data collection was carried out through interview techniques, observation, and documentation. The results show that the committee has a strategic role as program designers, activity organizers, value mentors, and facilitators of adolescent participation. Through the active involvement of adolescents in the planning, implementation, and evaluation processes of activities, the internalization of values such as responsibility, discipline, cooperation, leadership, and increased awareness in carrying out worship occurs. Thus, the management of structured and participation-based religious activities can make a significant contribution to the formation of adolescents' religious character.